2002
DOI: 10.1891/jcop.16.4.405.52529
|View full text |Cite
|
Sign up to set email alerts
|

Who Becomes a Depressive Ruminator? Developmental Antecedents of Ruminative Response Style

Abstract: Developmental antecedents of ruminative response style were examined in 137 college freshmen, who were followed prospectively for 2.5 years. Reports of mothers' and fathers' psychologically overcontrolling parenting as well as a history of childhood sexual (for women only) and emotional maltreatment were all related to ruminative response style. In addition, ruminative response style mediated the relationships between these developmental factors and the number of major depressive episodes experienced by partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
73
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 52 publications
(35 reference statements)
12
73
0
2
Order By: Relevance
“…Avoiding those maladaptive parenting responses is likely to benefit children’s mental health in several ways. These include reducing the chance that the children may develop negative cognition, adopt passive coping strategies (Muris et al, 2001; Spasojević and Alloy, 2002; Meesters and Muris, 2004; Brumariu and Kerns, 2010), and develop metacognitive beliefs about rumination, thereby reducing their risk to developing depression.…”
Section: Discussionmentioning
confidence: 99%
“…Avoiding those maladaptive parenting responses is likely to benefit children’s mental health in several ways. These include reducing the chance that the children may develop negative cognition, adopt passive coping strategies (Muris et al, 2001; Spasojević and Alloy, 2002; Meesters and Muris, 2004; Brumariu and Kerns, 2010), and develop metacognitive beliefs about rumination, thereby reducing their risk to developing depression.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this assumption, mothers' depressive rumination and (negative) family functioning have been found to be positively related to children's rumination [8,9]. Previous studies also found that parents who tend to discourage children's emotional autonomy in the face of negative events may lead them to engage in rumination, increasing their vulnerability to depression [45]. Considering previous literature on the cognitive and emotional profile of parents of children with SLD, it is plausible to hypothesize that if parents do not feel they have adequate parental skills and/or they are exposed to increased parental challenges because of specific difficulties of their child, they might encounter difficulties in encouraging children's emotional autonomy and positive coping styles, thus increasing the risk of rumination in their children.…”
Section: Relationships Between Parents' and Children's Emotional Profilementioning
confidence: 69%
“…20 Furthermore, in a female sample, Spaosjevic and Alloy found rumination to be a fully mediator of number of depressive episodes and sexual maltreatment. 21 These evidences support significant relations of rumination with childhood trauma and depression.…”
Section: Introductionmentioning
confidence: 75%